Clinical safety and performance of a MRI conditional pacing system in patients undergoing cardiac MRI. Issue 12 (5th December 2017) - Ching, Chi Keong; Chakraborty, Rabindra Nath; Kler, Tarlochan Singh; Pumprueg, Satchana; Ngarmukos, Tachapong; Chan, Joseph Yat Sun; Anand, Sumit; Yadav, Rakesh; Sitthisook, Surapun; Yim, Ka Wing; Jaswal, Rakesh K.; Bhargava, Kartikeya
Abstract: Background: Utilization of cardiac magnetic resonance imaging (cMRI) as an imaging modality in clinical practice is rapidly increasing. More evidence from randomized studies establishing clinical safety and performance of pacing systems in patients undergoing a cMRI scan is needed. Objectives: The purpose of this prospective, multicenter, randomized study was to demonstrate safety and efficacy of the Accent MRI™ conditional pacing systems (St. Jude Medical, St. Paul, MN, USA) in patients undergoing cMRI scan. Methods: Patients (n  =  283) indicated for dual‐chamber pacemaker implant were randomized to either the MRI Group (MG) (n  =  140) or the Control Group (CG) (n  =  143) after successful device implantation of the Accent MRI™ system. Clinical evaluation and device interrogation were performed at pre‐ and post‐MRI scan, and 1 month post‐MRI for all patients. At 9–12 weeks postimplant, patients in MG underwent a nondiagnostic cMRI scan at 1.5 Tesla (T), while patients in CG underwent device interrogation and clinical evaluation twice with a 45‐minute waiting period in between. The safety endpoint was freedom from MRI scan‐related complications and that for efficacy was significant changes in right atrial/ventricular capture threshold and sensing amplitude between right before MRI, immediately after MRI, and 1 month post‐MRI. Results: Results showed 100% freedom from MRI scan‐related complications. There were no significant changes in device performance between pre‐MRI scan and 1 month post‐MRI scan time points in both study groups. Conclusions: cMRI scanning with 1.5 T scanners is safe in patients implanted with the Accent MRI™ conditional pacing system and has no significant effect on the electrical parameters of the device and leads.